Effect of exhaust temperature on the performance of a diesel engine with EGR - Navindran, Subramaniam (2010)
The aim of this project is to determine the effect of the exhaust temperature on the performance of the diesel engine with exhaust gas recirculation (EGR) with respect to engine speed, throttle, biodiesel fuel and diesel fuel. Experiments have been performed for diesel fuel and bio-diesel fuel with 50% of throttle position for with and without EGR system. Engine brake torque, brake power and the exhaust temperature have been investigated for both fuels. All data were collected using data acquisition system which operates with Dewesoft software. The data were then exported to the Microsoft excel in order to construct graphs for performance analysis for each type of fuel and the engine conditions. From the analysis, it was found that the existence of EGR valve were reducing the exhaust temperature. Other than that, the torque produced by the engine with EGR valve were also lower than the engine without EGR valve. This shows that the exhaust temperature has an effect on the engine performance and allows the reduction of NOx formation.